Case study and empirical evidence for assessing natural resource management research : The experience of CIAT - Pachico, Douglas H.; Ashby, Jacqueline A.; Farrow, Andrew; Fujisaka, Sam; Johnson, Nancy L.; Winograd, Manuel (International Center for Tropical Agriculture, 1998)
The second section of the paper sketches out the broad outlines of some methodological approaches to NRM impact assessment. Ex ante approaches are considered, and some aspects of poverty measurement, extrapolation, and cross scale analysis are noted. The third and final section of the paper will present brief summaries of the findings of some studies focussing on the impact of NRM research.